Students' perceptions on learning ordinary differentialequations (ODEs) using MOOCs / Samsiah Abdul Razak ... [et al.] - Abdul Razak, Samsiah; Md Said, Junaida; G Arul, Elizabeth Selvamani; Yahya, Nur Azila; Jamian, Nurul Husna (Universiti Teknologi MARA, Perak, 2018)
In traditional Mathematics classes, the lecturer lectures and gives some examples related to the new concepts that have been taught. In order to get students more engaged and invested in their own learning, educators in UiTM Perak implemented the MOOC platform of Ordinary Differential Equations (MAT300) for teaching and learning of Ordinary Differential Equations. Students were assigned selected portions of learning materials in the MOOC platform before class. In this way, students were better prepared for class and class time was better utilized for discussions. Online learning here was used as a complement to and an extension of traditional classroom learning. MOOC make learning available to anyone anywhere at any time. This will also fulfills the education ministry's requirement of life-long learning for all. This study aims to investigate learner's perception in term of usefulness, understanding, effort, excitement and confident towards MOOC for Ordinary Differential Equations (ODE). This study involved 36 respondents from Diploma in Mathematical Sciences (CS143) students, who took MAT300 during the March- July 2017 semester. This study revealed that most of the students put in much effort accessing the online material, enjoyed learning through videos, preferred accessing MOOC on campus and had better understanding in MAT300 after using the MOOC platform. Overall, MOOC increased the level of confidence of students in learning MAT300.